Konsistensi penerapan aturan dan prosedur sebagai upaya pengembangan disiplin siswa kelas 1 untuk meningkatkan karakter profil pelajar Pancasila - Feri Tirtoni (COLLASE (Creative of Learning Students Elementary Education), 2026)
Abstract. The purpose of this study was to determine the consistency of the application of rules and procedures as an effort to develop discipline for grade 1 students to improve the character of the Pancasila student profile. The existence of this can motivate students' enthusiasm in practicing self-control. This research method is qualitative by means of a literature study, where the reviewer examines a theory related to the theme first. The reviewer then searches, collects information through books, articles, magazines, journals and other research results. The results show that there is an influence on consistency in the application of rules and procedures to form student’s discipline attitudes through the pancasila student profile resulting in a coefficient of 0,28 or 28%. This states the attitude of student discipline on the consistency that has been applied by teachers and student. That the purpose of strengthening the character building of Pancasila students through the consistent application of rules and procedures to encourage the emergence of good human beings with six main characteristics, namely critical thinking, creative, independent, devoted, devoted to God Almighty, noble character, mutual cooperation and global diversity. The hope is that students will be able to develop, make good use of their knowledge, seek knowledge, and understand or realize and behave in accordance with good character and morals manifested in their lives. With this, it is proven that it can shape a better personal character and make learning orderly when obeying the rules and procedures that have been set. Keywords - Consistent application of rules and procedures, Discipline, Pancasila Learner Profile